THE ANALYSIS OF LEADERSHIP EFFECT AND ORGANIZATIONAL CULTURE ON EMPLOYEES PERFORMANCE OF PANIN BANK - Harras, Hadyati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
The cause of employee performance up and down, due to many factors. including bad leadership and organizational culture. Therefore, this research was conducted to see the extent of phenomenon and how to solve it. The research approach used quantitative. The method of analysis uses descriptive and inferential. The number of samples in this study were 52 respondents, using the census sample method. The analysis method is multiple linear regression. The results show that leadership has a significant effect on performance with a regression coefficient of 0.484. Organizational culture has a significant effect on performance with a regression coefficient of 0.572. Leadership and organizational culture simultaneously have a significant effect on performance with a contribution value of 30.2 percent. This research confirms that leadership and organizational culture directly influence performance. But at the same time, leadership is perceived to be still low and the organizational culture is still conservative